Development of a mreB-targeted real-time PCR method for the quantitative detection of Vibrio harveyi in seawater and biofilm from aquaculture systems - Mougin, Julia; Roquigny, Roxane; Travers, Marie-Agnès; Grard, Thierry; Bonnin-Jusserand, Maryse; Le Bris, Cédric (Aquaculture, 2020)
Vibrio harveyi is a particularly problematic Gram-negative bacterium because it can form biofilms on aquaculture facility surfaces, leading to resistance of bacteria against antibiotics and water sanitizers. A SYBR Green I quantitative real-time PCR method was developed to detect V. harveyi directly from environmental samples, including seawater and biofilm. Specific primers targeting the mreB gene were designed. The exclusivity and inclusivity of the newly designed primers were evaluated using a panel of 85 bacteria: 58 V. harveyi from multiples origins and 27 non-V. harveyi isolates, and compared with two pairs of primers targeting the topA and toxR genes that were designed previously. All sets of primers were able to distinguish V. harveyi from closely related species belonging to the Harveyi clade. However, the mreB primers showed better inclusivity and were thus used to develop the real-time PCR assay. A quantification curve was obtained from pure culture of V. harveyi and exhibited excellent efficacy with detection levels as low as 5 genome copies in the PCR reaction. After selection of the extraction kit allowing the best DNA quantity and purity, validation was performed on both seawater and biofilm samples collected from a fish farm. The presence of inhibitors in the DNA templates was evaluated and a 10-fold dilution of template DNA was recommended in order to avoid their effects. The assay was able to detect V. harveyi from environmental samples, confirming the validity of the method. This real-time PCR method will help to evaluate the dynamics of V. harveyi in aquaculture facilities. Suitable prophylactic control measures could be designed using this method, instead of the use of curative methods such as antibiotics. •A real-time PCR was developed for quantification of V. harveyi in farming systems.•The method was tested on seawater and biofilm samples from a seabass farm.•New mreB primers were designed and revealed high specificity for V. harveyi.•The method will be useful for the epidemiological investigation of V. harveyi.